SEXUAL HEALTH FROM THE PERSPECTIVE OF ADOLESCENT SCHOOL PUPILS (Fiep Bulletin - online, 2014)
Adolescence is a period marked by intense transformations and accelerated physical growth and sexual maturation. Objectives: To identify the knowledge of sexual health, among adolescent students of a public secondary school; to identify the contraceptive methods used; and to assess the adolescents' level of satisfaction of adolescents concerning role of the school in sex education. Method: descriptive-exploratory field research with a quantitative approach, performed with 60 adolescents of a public school in the Brazilian municipality of Cajazeiras - PB. The study was approved by the Research Ethics Committee of the Faculdade Santa Maria under protocol no. 430022010. Data were collected through a questionnaire, organized in tables and analyzed in the light of the literature. The results indicate that (77%) of the respondents were female (46%) were in the 17 to 18 year age group, 50% were currently enrolled in the 1st year of middle school, and (48%) had family income roughly equivalent to the minimum wage. Only (23 %) showed good knowledge about sexuality, (38%) reported having an active sexual life, (97%) claimed to have had access to guidelines on sexuality, (95 %) mentioned the school as the main area of sexual guidance, through educational lectures, of which (90%) said they were satisfied with the school's performance in this area. However, although this high percentage of interviewees had received guidance, only (33%) used some method of contraception, with male and female condoms being the methods most often used (62.5%). Therefore, it is worth reflecting on the way in which sex education is being conducted; it should be initiated and given as soon as possible by parents and complemented by the school and professionals and health services that work with adolescents, in order to provide them with self-knowledge, so that they can make positive choices for their lives and the expression of their sexuality.
Keywords: Adolescents; Sexuality; Sexual Health.